Predictors of viral pneumonia in patients with community-acquired pneumonia. - Ji Eun Kim (PLoS ONE, 2014)
Background Viruses are increasingly recognized as major causes of community-acquired pneumonia (CAP). Few studies have investigated the clinical predictors of viral pneumonia, and the results have been inconsistent. In this study, the clinical predictors of viral pneumonia were investigated in terms of their utility as indicators for viral pneumonia in patients with CAP. Methods Adult patients (≥ 18 years old) with CAP, tested by polymerase chain reaction (PCR) for respiratory virus, at two teaching hospitals between October 2010 and May 2013, were identified retrospectively. Demographic and clinical data were collected by reviewing the hospital electronic medical records. Results During the study period, 456 patients with CAP were identified who met the definition, and 327 (72%) patients were tested using the respiratory virus PCR detection test. Viral pneumonia (n = 60) was associated with rhinorrhea, a higher lymphocyte fraction in the white blood cells, lower serum creatinine and ground-glass opacity (GGO) in radiology results, compared to non-viral pneumonia (n = 250) (p < 0.05, each). In a multivariate analysis, rhinorrhea (Odd ratio (OR) 3.52; 95% Confidence interval (CI), 1.58-7.87) and GGO (OR 4.68; 95% CI, 2.48-8.89) were revealed as independent risk factors for viral pneumonia in patients with CAP. The sensitivity, specificity, positive- and negative-predictive values (PPV and NPV) of rhinorrhea were 22, 91, 36 and 83%: the sensitivity, specificity, PPV and NPV of GGO were and 43, 84, 40 and 86%, respectively. Conclusion Symptom of rhinorrhea and GGO predicted viral pneumonia in patients with CAP. The high specificity of rhinorrhea and GGO suggested that these could be useful indicators for empirical antiviral therapy.